(x + 1)(x + 3)(x + 4)(x + 6)= 112を解く?

(x + 1)(x + 3)(x + 4)(x + 6)= 112を解く?
Anonim

回答:

x = -7 / 2 + -isqrt31 / 2 または x = -7 / 2 + -sqrt57 / 2

説明:

LHSを以下のようにグループ化しましょう。

(x + 1)(x + 6)(x + 3)(x + 4)= 112

=>(x ^ 2 + 7x + 6)(x ^ 2 + 7x + 12)= 112

今させましょう u = x ^ 2 + 7x そして上記の式は

(u + 6)(u + 12)= 112

または u ^ 2 + 18u + 72 = 112

または u ^ 2 + 18u-40 = 0

または (u + 20)(u-2)= 0 すなわち u = 2 または -20

それなりに x ^ 2 + 7x + 20 = 0 すなわち x =( - 7 + -sqrt(7 ^ 2-80))/ 2 すなわち x = -7 / 2 + -isqrt31 / 2

または x ^ 2 + 7x-2 = 0 すなわち x =( - 7 + -sqrt(7 ^ 2 + 8))/ 2 すなわち x = -7 / 2 + -sqrt57 / 2